CLINICAL PRESENTATION AND MANAGEMENT OF VISCERAL LEISHMANIASIS - Tanoli, Zardad Muhammad; Rai, Manzoor Elahi; Gandapur, Abdus Salam Khan (Journal of Ayub Medical College Abbottabad, 2005)
Background: Febrile illnesses like malaria, typhoid, and tuberculosis are the commonest problems in our area, but visceral leishmaniasis (VL) is also one of the diseases presenting with fever in this part of the country. This study was conducted to evaluate its clinical spectrum and way of management. Methods: This study was conducted in Paediatric Department of Women and Children Hospital and Ayub Teaching Hospital, Abbottabad from October 1985 to August 1999 during which 70 cases of VL were diagnosed and managed. Results: All patients were below 10 years of age and were from Hazara division. Majority of them were from two specific localities, one in Abbottabad District (43%) and the other in Mansehra District (14%). Common clinical features were Fever 99%, Splenomegaly (99%), Anaemia (96%), Hepatomegaly (86%), distension of abdomen (47%) and bleeding diathesis 14%. Haemoglobin was below 7.9 gm in 82.86%, white cell count was below 4000/mm3 in 42.85%, Platelet count was below 100000/mm3 in 67.14% and ESR was >50 mm at the end of first hour in 86% of the patients. All the patients showed Leishmania Donovani bodies in the bone marrow smears except one, where tap was dry and then trephine biopsy was performed to confirm the diagnosis. In 67 cases amastigote form was found and only in 3 patients the promastigotes were found. Fifty two patients had received meglumine antimoniate (glucantime) and 18 received sodium stibogluconate (pentostam) along with supportive therapy. Mortality was 11.43%. Conclusions: The disease is gradually spreading southwards in the country. Children below 5 years are mainly affected. Bone marrow examination is the most reliable and simple method of diagnosis. A high index of suspicion must he kept in mind for all febrile cases coming from Hazara division, Northern areas, Azad Kashmir. Keywords: Leishmaniasis, Visceral Leishmaniasis, Febrile Illness